Level of Psychological Well- Being in a sample of adolescents with obesity - baali, moustafa (Journal of Social Sciences and Humanities, 2021)
The study aimed to identify the level of the orientation of the life in a sample of adolescents with obesity. The researcher selected for this study a sample of (76) of adolescents with obesity, and relied on tools to collect data were represented in the measure of obesity (height, weight, body mass), and the scale of the orientation of the life Preparation by Dr.Yasera Abo Hadroos, the following results: -1The level of Psychological Well- Being, in adolescents with obesity is high. -2 There were no statistically significant differences in the level of life orientation among adolescents with obesity by sex.